Goya on Sexual Violence: Testimony and Critique - Iarocci, Michael (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2022)
This essay examines three prints from Goya’s Disasters of War to elucidate the complex moral analyses that the artist develops over the course of his famous print series. While the Disasters of War have often been understood as forms of historical testimony, the essay argues that the series is better understood within the eighteenth-century coordinates of critique and satire. It focuses on prints dedicated to sexual violence to underscore the dense layering of meanings that Goya achieves through: a) the sequential presentation of his image; b) the interplay between captions and images; and c) the combination of realist pictorial codes and abstraction.